Experimental evaluation of periodic output feedback control for SMA actuated structures. (29th November 2010) - Dhanalakshmi, K.; Umapathy, M.; Ezhilarasi, D.; Marimuthu, M.
This paper presents the design and experimental evaluation of periodic output feedback controller to minimise structural vibration of a cantilever beam using shape memory alloy (SMA) wires as control actuators and piezoceramics as sensor and disturbance actuator. Online recursive least square parameter estimation is used to obtain linear dynamic models of the smart cantilever beam. Simulink™ modelling software and dSPACE DS1104 controller board are used for identification and control. The performance of the controller is evaluated experimentally at resonance.